2023
DOI: 10.3390/app13148465
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lightweight YOLOv4 Foreign Object Detection Method for Conveyor Belts Combined with CBAM

Abstract: During the operation of the belt conveyor, foreign objects such as large gangue and anchor rods may be mixed into the conveyor belt, resulting in tears and fractures, which affect transportation efficiency and production safety. In this paper, we propose a lightweight target detection algorithm, GhostNet-CBAM-YOLOv4, to resolve the problem of the difficulty of detecting foreign objects at high-speed movement in an underground conveyor belt. The Kmeans++ clustering method was used to preprocess the data set to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Figure 1 shows a schematic diagram of the environment. The empirical data revealed that conveyor belt system had been a focus of numerous studies in terms of researching the actual amount of material on belt [4][5][6], tracking the movements [7][8][9], checking for product quality, detecting faults, speed regulation strategy and variable belt-speed energy issue for energy saving [10], etc. These researches discuss various techniques for extracting the material from the belt through computer vision techniques, such as background subtraction, canny edge detection, and morphological operations for analysis and quantification of the material to perform further processes on it to achieve their desired goals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic diagram of the environment. The empirical data revealed that conveyor belt system had been a focus of numerous studies in terms of researching the actual amount of material on belt [4][5][6], tracking the movements [7][8][9], checking for product quality, detecting faults, speed regulation strategy and variable belt-speed energy issue for energy saving [10], etc. These researches discuss various techniques for extracting the material from the belt through computer vision techniques, such as background subtraction, canny edge detection, and morphological operations for analysis and quantification of the material to perform further processes on it to achieve their desired goals [4].…”
Section: Introductionmentioning
confidence: 99%